Transition metal sulfide adsorbent as well as preparation method and application thereof

By using the transition metal sulfide adsorbent prepared by the molybdenum-based metal organic frame and thiourea calcination, the problem of insufficient adsorption capacity and stability of existing adsorbents when removing Ag+ is solved, and efficient selective removal and resources of Ag+ are achieved. Recycling.

CN119455886AActive Publication Date: 2025-02-18JINGGANGSHAN UNIVERSITY

Patent Information

Application Number
CN202411787870.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-18
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

When removing Ag+ from water, the existing adsorbent has low adsorption capacity, poor reusability and stability, and the preparation process is complicated, resulting in a large amount of toxic acid and alkali waste liquid.

Method used

Molybdenum-based metal organic frame (Mo-MOF) is used as a template and calcined with thiourea. Transition metal sulfide adsorbent is prepared by high-temperature template cracking method to create an active center that has both adsorption and reduction.

Benefits of technology

It realizes efficient selective removal of Ag+ in water bodies, provides a porous adsorption material with both selective and reducing adsorption sites, ensuring the safety of the water environment and the green and low-carbon circulation of silver resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455886A_ABST
    Figure CN119455886A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorbent materials, in particular to a transition metal sulfide adsorbent and a preparation method and application thereof.According to the transition metal sulfide adsorbent, Mo-MOF serves as a template, thiourea and Mo-MOF are calcined according to the mass ratio of 3-4: 1, and the transition metal sulfide adsorbent is prepared through a high-temperature template cracking method; an active center with adsorption and reduction functions is created on an adsorption material reaction interface by utilizing an MOF template high-temperature cracking method, and the prepared MOF template derived transition metal sulfide adsorption material can realize efficient selective removal and resource recycling of Ag < + > in a water body; the method has important significance for guaranteeing the safety of the water environment and maintaining the development of green and low-carbon circular economy of silver resources. And a prototype new technology integrating selective adsorption and heavy metal elementary substance is provided for a wastewater heavy metal low-carbonization technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbent materials, and in particular to a transition metal sulfide adsorbent and a preparation method and application thereof. Background Art

[0002] As an important precious metal, silver is widely used in the fields of medicine, electronics, and chemicals. The latest data from the World Silver Association shows that global demand for silver has increased by 16% year-on-year, and the silver gap is as high as 194 million ounces. However, limited mines have led to a shortage of silver resources, and silver-containing wastewater, which accounts for about 10% of the raw materials each year, inevitably enters the water environment. If these silver-containing wastewaters are not treated, on the one hand, it will cause environmental pollution, and on the other hand, it will also lead to a huge waste of silver resources. Therefore, the recycling of silver resources is crucial to maintaining the integrity of the future supply chain and reducing environmental pollution.

[0003] Methods for removing and recovering silver from water bodies include cyanide solution or nitric acid extraction, ion exchange, reverse osmosis and adsorption. However, these methods will cause further environmental problems, such as the use of large amounts of chemical reagents, the generation of waste acid solutions and toxic fumes. Some studies have considered Ag + The process of reducing AgCl or Ag2SO4 to silver metal is complicated, involving high carbon emissions and high energy consumption. In comparison, the adsorption method is considered to be the most cost-effective and environmentally friendly method for Ag. + A competitive technical means of removal.

[0004] Currently reported adsorbents such as activated carbon, fly ash, expanded perlite, biosorbents, and electrospinning have been used for Ag removal in water. + However, these traditional adsorbents often have the disadvantages of low adsorption capacity, poor reusability and stability. In addition, the adsorbent materials prepared by existing methods are usually poor in adsorption of Ag. + After completion, it needs to be eluted, regenerated and then restored. The whole process is cumbersome and complicated and produces a large amount of toxic acid and alkali waste liquid. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a transition metal sulfide adsorbent and a preparation method and application thereof. The transition metal sulfide adsorbent of the present invention uses Mo-MOF as a template, mixes thiourea and Mo-MOF, and utilizes a high-temperature template pyrolysis method to prepare the transition metal sulfide adsorbent.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0008] The Mo-MOF template was synthesized by hydrothermal method.

[0009] Under a protective atmosphere, thiourea and the Mo-MOF template are placed on one side of a tube furnace and at the center of a heat source in a mass ratio of 3 to 4:1, respectively, and heated to obtain a transition metal sulfide adsorbent through a high-temperature template cracking method.

[0010] The present invention uses a molybdenum-based metal organic framework as a template, calcines it with thiourea, and uses a high-temperature pyrolysis method to create an active center with both adsorption and reduction at the reaction interface of the adsorption material. The prepared transition metal sulfide adsorption material derived from the molybdenum-based metal organic framework template can achieve the adsorption of Ag in water. + Highly efficient and selective removal. The present invention can inherit the large specific area and abundant pores of the original molybdenum-based metal organic framework through the template method, which is conducive to providing sufficient sites and transmission channels; the unstable coordination structure can be calcined by high-temperature calcination to form a stable framework, and the H2S decomposed by thiourea at high temperature can react with the Mo on the molybdenum-based metal organic framework. 4+ To form molybdenum sulfide, S atoms can react with Ag + The formation of Ag2S, and S can reduce Ag + , while Ag + The potential is higher than Mo 4+ , Ag + As a weak oxidant, it can oxidize Mo 4+ , Ag + Reduction to elemental Ag 0 Therefore, the transition metal sulfide adsorbent of the present invention has a great influence on Ag + It has excellent adsorption selectivity.

[0011] In a preferred embodiment of the present invention, the heating temperature is 1000° C. to 1200° C., and the calcination time is 1 hour to 1.2 hours.

[0012] In a preferred embodiment of the present invention, the method for preparing the Mo-MOF template comprises the following steps:

[0013] The molybdenum source is dissolved in water to form a uniformly dispersed solution.

[0014] Imidazole is added to the uniformly dispersed solution, heated for reaction, and a Mo-MOF template is obtained through post-treatment.

[0015] In a preferred embodiment of the present invention, the volume ratio of the molybdenum source mass to water is 4g:0.1L~0.3L.

[0016] In a preferred embodiment of the present invention, the mass ratio of imidazole to molybdenum source is 4:1-2.

[0017] In a preferred embodiment of the present invention, the heating reaction temperature is 100° C. to 200° C., and the heating reaction time is 12 h to 72 h.

[0018] The second object of the present invention is to provide a transition metal sulfide adsorbent prepared by any of the preparation methods described above.

[0019] In a preferred embodiment of the present invention, the transition metal sulfide adsorbent is a nanorod structure with a length of 10 μm to 20 μm and a diameter of 1 μm to 2 μm.

[0020] The third object of the present invention is to provide an application of the above-mentioned transition metal sulfide adsorbent in the targeted adsorption of silver in silver-containing wastewater.

[0021] In a preferred embodiment of the present invention, the concentration of the silver-containing wastewater is 50 mg / L to 2000 mg / L, and the usage ratio of the transition metal molybdenum sulfide adsorbent to the silver-containing wastewater is 1 mg: 2 mL to 4 mL.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention uses a molybdenum-based metal organic framework as a template, calcines it with thiourea, and uses a high-temperature pyrolysis method to create an active center with both adsorption and reduction at the reaction interface of the adsorption material. The prepared transition metal sulfide adsorption material derived from the molybdenum-based metal organic framework template can achieve the adsorption of Ag in water. + Highly efficient and selective removal. The present invention can inherit the large specific area and abundant pores of the original molybdenum-based metal organic framework through the template method, which is conducive to providing sufficient sites and transmission channels; the unstable coordination structure can be calcined by high-temperature calcination to form a stable framework, and the H2S decomposed by thiourea at high temperature can react with the Mo on the molybdenum-based metal organic framework. 4+ To form molybdenum sulfide, S atoms can react with Ag + The formation of Ag2S, and S can reduce Ag + , while Ag + The potential is higher than Mo 4+ , Ag + As a weak oxidant, it can oxidize Mo 4+ , Ag + Reduction to elemental Ag 0 Therefore, the transition metal sulfide adsorbent of the present invention has a great influence on Ag + It has excellent adsorption selectivity.

[0024] 2. The present invention uses Mo-MOF as a template to construct a derived transition metal sulfide adsorption material, thereby providing a porous adsorption material with both selective and reductive adsorption sites in one position for Ag +The resource utilization of silver is of great significance for ensuring water environment safety and maintaining the development of a green, low-carbon circular economy of silver resources. It provides a new prototype technology that integrates selective adsorption and heavy metal elementalization for the low-carbonization technology of heavy metals in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a preparation process diagram of the present invention.

[0026] Figure 2 These are morphology diagrams of transition metal sulfide adsorbent materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3 of the present invention.

[0027] Figure 3 This is a graph showing the adsorption capacity results of the transition metal sulfide adsorbent materials thiourea and Mo-MOF at different ratios prepared in Examples 1 and 3 of the present invention and Comparative Examples 4 and 5.

[0028] Figure 4 This is a graph showing the adsorption capacity results of the transition metal sulfide adsorbent materials prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 to 3 at different calcination temperatures.

[0029] Figure 5 The transition metal sulfide adsorbent prepared in Example 1 of the present invention is used for Ag in the presence of coexisting ions. + Affinity diagram. DETAILED DESCRIPTION

[0030] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0032] Metal-organic frameworks and transition metal sulfides are representatives of porous materials. +It shows outstanding application prospects in removal. Metal-organic frameworks are an emerging class of porous crystalline solids, in which metal ions or metal clusters are combined with organic ligands through organic linkers, and have high porosity and open nodes. However, the coordination bonds between metal active centers and organic ligands in metal-organic framework adsorbents are often fragile, which makes the metal-organic framework unstable in water, resulting in structural collapse and thus site failure, reducing its adsorption performance. Transition metal sulfides are endowed with high interfacial reaction activity due to the size homogenization effect. However, transition metal sulfides are easy to agglomerate in water, resulting in limited exposed sites or insufficient site utilization. Therefore, the present invention provides a transition metal sulfide adsorbent, wherein the transition metal sulfide uses Mo-MOF as a template, calcines thiourea and Mo-MOF in a mass ratio of 3 to 4:1, and prepares the transition metal sulfide adsorbent by a high-temperature template pyrolysis method. The preparation process is as follows: Figure 1 As shown in the figure, active centers with both adsorption and reduction properties are created at the reaction interface of the adsorbent material. The prepared MOF template-derived transition metal sulfide adsorbent material can achieve the adsorption of Ag in water. + The present invention can inherit the large specific area and abundant pores of the original Mo-MOF through the template method, which is conducive to providing sufficient sites and transmission channels; high-temperature calcination can calcine the unstable coordination structure to form a stable framework, and the H2S decomposed by thiourea at high temperature can react with the Mo on the Mo-MOF. 4+ To form molybdenum sulfide, S atoms can react with Ag + The formation of Ag2S, and S can reduce Ag + ; At the same time Ag + The potential is higher than Mo 4+ , Ag + As a weak oxidant, it can oxidize Mo 4+ , Ag + Reduction to elemental Ag 0 Therefore, the transition metal sulfide adsorbent of the present invention has a great influence on Ag + It has excellent adsorption selectivity.

[0033] Example 1

[0034] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0035] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0036] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0037] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0038] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0039] (5) The thiourea is transferred to a porcelain boat labeled No. 1 and the Mo-MOF is weighed in porcelain boats labeled No. 1 and No. 2, respectively, at a mass ratio of 3:1. The two raw materials need to be evenly spread in their respective magnetic boats.

[0040] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1000℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0041] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent, named MS-1000.

[0042] Example 2

[0043] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0044] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0045] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0046] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0047] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0048] (5) The thiourea is transferred to the porcelain boat marked as No. 1 and the Mo-MOF is weighed in the porcelain boats marked as No. 1 and No. 2 respectively in a mass ratio of 3:1. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0049] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 on the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first introduce argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1200℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0050] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent, named MS-1200.

[0051] Example 3

[0052] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0053] (1) Weigh 0.89 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir ultrasonically for 10 min to form a uniformly dispersed solution.

[0054] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0055] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0056] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0057] (5) The thiourea is transferred to the porcelain boat marked as No. 1 and the Mo-MOF is weighed in the porcelain boats marked as No. 1 and No. 2 respectively in a mass ratio of 4:1. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0058] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1000℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0059] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, and then grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent.

[0060] Example 4

[0061] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0062] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 20 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0063] (2) Add 0.4 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0064] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 100°C, and condensed water was introduced for condensation reflux. The reaction time was 72 h, and the mechanical stirring speed was controlled at 300 rpm.

[0065] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0066] (5) The thiourea is transferred to a porcelain boat labeled No. 1 and the Mo-MOF is weighed in porcelain boats labeled No. 1 and No. 2, respectively, at a mass ratio of 3:1. The two raw materials need to be evenly spread in their respective magnetic boats.

[0067] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1000℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0068] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, and then grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent.

[0069] Example 5

[0070] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0071] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 40 mL of deionized water and 100 mL of solvent, and stir ultrasonically for 10 min to form a uniformly dispersed solution.

[0072] (2) Add 0.3 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0073] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 200°C, and condensed water was introduced for condensation reflux. The reaction time was 12 h, and the mechanical stirring speed was controlled at 300 rpm.

[0074] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0075] (5) The thiourea is transferred to a porcelain boat labeled No. 1 and the Mo-MOF is weighed in porcelain boats labeled No. 1 and No. 2, respectively, at a mass ratio of 3:1. The two raw materials need to be evenly spread in their respective magnetic boats.

[0076] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1000℃ and heat it at 5℃min. -1The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0077] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, and grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent.

[0078] Comparative Example 1

[0079] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0080] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0081] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0082] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0083] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0084] (5) The thiourea is transferred to the porcelain boat marked as No. 1 and the Mo-MOF is weighed in the porcelain boats marked as No. 1 and No. 2 respectively in a mass ratio of 3:1. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0085] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 400℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0086] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent, named MS-400.

[0087] Comparative Example 2

[0088] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0089] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0090] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0091] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0092] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0093] (5) The thiourea is transferred to the porcelain boat marked as No. 1 and the Mo-MOF is weighed in the porcelain boats marked as No. 1 and No. 2 respectively in a mass ratio of 3:1. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0094] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 600℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0095] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent, named MS-600.

[0096] Comparative Example 3

[0097] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0098] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0099] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0100] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0101] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0102] (5) The thiourea is transferred to the porcelain boat marked as No. 1 and the Mo-MOF is weighed in the porcelain boats marked as No. 1 and No. 2 respectively in a mass ratio of 3:1. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0103] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first introduce argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 800℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0104] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent, named MS-800.

[0105] Comparative Example 4

[0106] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0107] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0108] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0109] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0110] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0111] (5) The thiourea is transferred to a porcelain boat labeled No. 1 and the Mo-MOF is weighed in a weight ratio of 1:1 in porcelain boats labeled No. 1 and No. 2, respectively. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0112] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1000℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0113] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, and grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent.

[0114] Comparative Example 5

[0115] A method for preparing a transition metal sulfide adsorbent comprises the following steps:

[0116] (1) Weigh 0.8 g of molybdenum trioxide and dissolve it in a single-necked flask containing 60 mL of deionized water and 100 mL of solvent, and stir it ultrasonically for 10 min to form a uniformly dispersed solution.

[0117] (2) Add 0.2 g of imidazole to the uniformly dispersed solution until fully mixed, and then continue ultrasonic stirring for 10 minutes.

[0118] (3) A polytetrafluoroethylene magnetic stirring bar was placed on the three-necked flask, and the single-necked flask containing the mixture was transferred to a constant temperature oil bath for heating reaction. The oil bath temperature was controlled at 120°C, and condensed water was introduced for condensation reflux. The reaction time was 24 h, and the mechanical stirring speed was controlled at 300 rpm.

[0119] (4) After the reaction is completed, the single-necked flask is cooled at room temperature, the white precipitate in the single-necked flask is filtered, and the precipitate is washed three times with deionized water and three times with ethanol. Finally, the white solid is dried in a vacuum drying oven at 80° C. for 24 h. The white powder obtained by grinding is Mo-MOF.

[0120] (5) The thiourea is transferred to the porcelain boat marked as No. 1 and the Mo-MOF is weighed in the porcelain boats marked as No. 1 and No. 2 respectively in a mass ratio of 2:1. At the same time, the two raw materials need to be evenly spread in their respective magnetic boats.

[0121] (6) Place the porcelain boat marked as No. 1 on the upstream side of the tube furnace, that is, on the side of the argon inlet, and place the porcelain boat marked as No. 2 at the heat source center of the tube furnace. The two porcelain boats are adjacent to each other. Before heating the tube furnace, first pass argon gas for 1 hour to remove the oxygen in the tube furnace. After removing the oxygen in the tube furnace, set the temperature of the tube furnace to 1000℃ and heat it at 5℃min. -1 The temperature was programmed to rise at a rate of , and the tube furnace was heated under Ar gas protection, and the high temperature calcination was continued for 1 h.

[0122] (7) Stop the reaction, wait for the mixture to cool naturally to room temperature, and then grind and collect the black product after the reaction to obtain a transition metal sulfide adsorbent.

[0123] Results Analysis

[0124] Preparation of adsorption solution

[0125] Ag + The solution was prepared by dissolving silver nitrate in ultrapure water. + Solution preparation and determination: ① Prepare 2.0 gL -1 Ag + Stock solution: Dissolve 3.1496g AgNO3 in 1L ultrapure water and store in refrigerator. + Solution: Dilute 2.0 g L with deionized water -1 Ag + Stock solution to obtain an initial concentration range of 50-2000 mg·L -1 Ag + ③Prepare and determine Ag + Solution standard curve: Dilute Ag with 1% HNO3 solution + Solution, 6 different concentrations of Ag were obtained + Standard solution, concentration range 0~6mg L -1 The measurement was carried out using a continuous light source atomic absorption spectrometer ContrAA 700, with absorbance as the ordinate. +The solution concentration is the horizontal axis, and the straight line is Ag. + Solution standard curve. ④ Ag in solution + Concentration determination: Determination of Ag in water samples using continuous light source atomic absorption spectrometer + concentration, used to evaluate the adsorbent's ability to react with Ag + All experiments were performed three times, and the final data is the average of the three experiments.

[0126] Figure 2 The SEM morphology of the transition metal sulfide adsorbent material prepared by Examples 1-2 and Comparative Examples 1-3 of the present invention shows that the adsorbent material has a nanorod structure. As the reaction temperature increases, the generated nanorods become irregular, with a length of about 10μm-20μm and a diameter of 1μm-2μm. When the calcination temperature is increased from 400°C to 800°C, sporadic fragments appear on the surface. When calcined at 1000°C, a dense structure formed by a large number of fragments accumulates on the surface, and a multi-layer "cabbage" structure is formed inside from the cross section. This layered form is a typical MoS2 structure, and there are a large number of fragments and particles embedded in the nanorods. When calcined at 1200°C, the nanorods become very thin, and the high temperature causes a large amount of cracking on the surface. In addition, the corresponding EDX-mapping can see the presence of the S element, which is the result of the reaction of H2S produced by the decomposition of thiourea at high temperature with MOF. The adsorbent synthesized using Mo-MOF as a template maintains some of the morphology and structure of the original MOFs. The nanorod substrate can not only disperse the MoS2 nanosheets well, but also expose more edge active sites, making the material more resistant to Ag. + The removal performance is greatly improved.

[0127] Weigh 20 mg of four different proportions of adsorbent material and add them to 80 mL of 2000 mg / L agar. + The sample was oscillated in a constant temperature oscillator at 298 K for 12 h, with the speed set at 180 rpm. After the oscillation was balanced, the sample was filtered through a 0.22 μm polyethersulfone membrane to obtain the supernatant, and the Ag before and after adsorption was determined using a ContrAA 700 high-resolution continuous light source atomic absorption spectrometer. + concentration.

[0128] Figure 3The adsorption capacity results of thiourea and Mo-MOF at different ratios of the transition metal sulfide adsorbent materials prepared in Examples 1 and 3 of the present invention and Comparative Examples 4 and 5 are shown. It can be seen from the figure that the adsorption performance of thiourea and Mo-MOF materials with a ratio of 3:1 and 4:1 is the best. This is mainly because excess thiourea can decompose thiourea at high temperature and fully contact the molybdenum atoms on Mo-MOF to form molybdenum sulfide. Since the number of exposed molybdenum atoms is limited, even if more thiourea is decomposed, the molybdenum sulfide formed is certain, so the adsorption amount no longer increases.

[0129] Isothermal adsorption: 20 mg of adsorbent nanorods calcined at different temperatures were added to 80 mL of Ag with different concentrations. + The isothermal adsorption experiments of Sb(V) were conducted at different temperatures of 283K, 298K and 318K, and the samples were shaken in a constant temperature oscillator for 12 hours at a speed of 180 rpm. + The initial concentration was 50 mg L -1 , 100mg L -1 , 200mg L -1 , 400mg L -1 , 600mg L -1 , 800mg L -1 , 1000mg L -1 , 1200mg L -1 , 1400mg L -1 , 1600mg L -1 , 1800mg L -1 , 2000mg L -1 After adsorption equilibrium, the sample was filtered through a 0.22 μm polyethersulfone membrane to obtain the supernatant, and the Ag before and after adsorption was determined using a ContrAA 700 high-resolution continuous light source atomic absorption spectrometer. + concentration.

[0130] Figure 4 The adsorption capacity results of the transition metal sulfide adsorbent materials prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 to 3 at different calcination temperatures are shown in FIG. Figure 4 It can be seen that the MS-400, MS-600, MS-800, MS-1000 and MS-1200 nanorods have a significant effect on Ag + The removal capacity was 172.1 mg g -1 , 250.2mg g -1 , 484.8mg g -1 , 2315.6mg g -1 and 1860mg g -1MS-1000 obtained an ultra-high adsorption capacity superior to the other four materials, which is almost 13 times that of MS-400, indicating that the nanorods generated at a calcination temperature of 1000°C have a high adsorption capacity for Ag. + The removal effect is the best. This is mainly because two different crystal phases of molybdenum sulfide 1T and 2H phases are formed at 1000℃. 1T phase molybdenum sulfide can reduce Ag + , the 2H phase of MoS provides a layered structure that is beneficial to Ag + transported to the adsorption site and formed coordination.

[0131] 20 mg of MS-1000 nanorod adsorbent was added to 20 mL of K + , Ca 2+ Mg 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Cd 2+ 、Zn 2+ , Pb 2+ and Ag + The 10 ion concentrations were all 1 mmol / L in a mixed solution. The mixture was shaken in a 298K constant temperature shaker for 12 hours. After adsorption equilibrium, the supernatant was collected by pinhole filter membrane filtration, and the concentration of each component ion in the supernatant was determined using a ContrAA 700 high-resolution continuous light source atomic absorption spectrometer.

[0132] In Ag + and interfering ions K + Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ 、Cd 2+ , Cu 2+ and Pb 2+ In the mixture of + The removal of MS-1000 nanorods and Ag + The affinity of d Come and evaluate, K d It is an important indicator to measure the selectivity of the adsorbent. d Value 1.0×10 5 mL g -1 It can determine the selectivity of the adsorbent. Figure 5 In the presence of coexisting ions, the transition metal sulfide adsorbent prepared in Example 1 of the present invention is used to absorb Ag. + The affinity diagram shows that the MS-1000 nanorod adsorbent can completely separate silver ions from other metal ions in a mixed solution, indicating that the MS-1000 nanorod adsorbent still has good affinity for Ag in a complex silver-containing solution.+ It has excellent selectivity. This is mainly because as the calcination temperature increases, more Mo atoms are exposed and more molybdenum sulfide is formed. When it exceeds 1000°C, the structure of MOF breaks down and it is difficult to maintain the growth of more sites, resulting in a decrease in the adsorption amount.

[0133] In summary, the present invention uses the MOF template high temperature pyrolysis method to create active centers with both adsorption and reduction at the reaction interface of the adsorbent material. The prepared MOF template-derived transition metal sulfide adsorbent material can achieve the adsorption of Ag in water. + Efficient selective removal and resource recovery are of great significance for ensuring water environmental safety and maintaining the development of a green, low-carbon circular economy of silver resources. It provides a new prototype technology that integrates selective adsorption and heavy metal elementalization for wastewater heavy metal low-carbonization technology.

[0134] It should be noted that when the present invention relates to a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundant description, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments. Therefore, the attached protection scope is intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.

[0135] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations.

Claims

1. A method for preparing a transition metal sulfide adsorbent, characterized in that: The following steps are involved: The Mo-MOF template was synthesized using a hydrothermal method; Under a protective atmosphere, thiourea and the Mo-MOF template are calcined in a mass ratio of 3 to 4:1, and a transition metal sulfide adsorbent is obtained by a high-temperature template cracking method.

2. The method for preparing a transition metal sulfide adsorbent according to claim 1, characterized in that: The calcination temperature is 1000° C. to 1200° C., and the calcination time is 1 hour to 1.2 hours.

3. The method for preparing a transition metal sulfide adsorbent according to claim 1, characterized in that: The preparation method of the Mo-MOF template comprises the following steps: dissolving a molybdenum source in water to form a uniformly dispersed solution; Imidazole is added to the uniformly dispersed solution, heated for reaction, and a Mo-MOF template is obtained through post-treatment.

4. The method for preparing a transition metal sulfide adsorbent according to claim 3, characterized in that: The volume ratio of the molybdenum source mass to water is 4g:0.1L~0.3L.

5. The method for preparing a transition metal sulfide adsorbent according to claim 3, characterized in that: The mass ratio of imidazole to molybdenum source is 4:1-2.

6. The method for preparing a transition metal sulfide adsorbent according to claim 3, characterized in that: The heating reaction temperature is 100°C to 200°C, and the heating reaction time is 12h to 72h.

7. A transition metal sulfide adsorbent prepared by the preparation method according to any one of claims 1 to 6.

8. The transition metal sulfide adsorbent according to claim 7, characterized in that: The transition metal sulfide adsorbent is a nanorod structure with a length of 10 μm to 20 μm and a diameter of 1 μm to 2 μm.

9. Use of the transition metal sulfide adsorbent according to claim 7 in targeted adsorption of silver in silver-containing wastewater.

10. The use according to claim 9, characterized in that: The concentration of the silver-containing wastewater is 50 mg / L to 2000 mg / L, and the usage ratio of the transition metal sulfide adsorbent to the silver-containing wastewater is 1 mg: 2 mL to 4 mL.

Citation Information

Patent Citations

  • Application of fish-scale shaped transition metal sulfide carbon nanomaterial

    CN110270305A

  • Hollow carbon shell inlaid with metal sulfide, preparation method and application thereof

    CN113809323A

  • Adsorbent for fixing molybdenum disulfide through multistage network of different components and preparation method and application thereof

    CN115582103A

  • Preparation method of Mo-MoF-derived MoS2 rodlike structure composite B-doped g-C3N4 sheet photocatalyst

    CN116586092A

  • Metal-organic framework templated synthesis of porous inorganic materials as novel sorbents

    US20140319058A1

Cited By

  • Magnetic transition metal sulfide adsorption material as well as preparation method and application thereof

    CN121060465A